A new species of Ophthalmoblysis Scoble, 1995 (Geometridae: Ennominae) from México with ‘sleepy’ eyespots - Garzón-Orduña, Ivonne J. (Zootaxa, 2019)
A new species of Ophthalmoblysis Scoble, 1995 from Mexico is described and illustrated: O. ibarrai Garzón-Orduña, sp.n. The species is known only from Los Tuxtlas (Veracruz, Mexico), and is distinguished by the shape and pattern of the hindwing eyespot. Unlike the eyespot of other species in Ophthalmoblysis, that of O. ibarrai has a smaller and not fully circular inner black disc. In addition, O. ibarrai can be distinguished from a similar, undescribed species from Costa Rica by the presence of a sclerotized extension at the tip of the male valva and by the shape of the cornutus in the vesica. Ophthalmoblysis ibarrai represents the northernmost member of the genus.